2011
DOI: 10.1007/s10103-011-0996-9
|View full text |Cite
|
Sign up to set email alerts
|

The role of vascular endothelial growth factor in fractional laser resurfacing with the carbon dioxide laser

Abstract: The aim of this study was to analyze the role of vascular endothelial growth factor (VEGF) in mechanisms of cutaneous remodeling induced by fractional CO(2) laser treatment. The dorsal skin of Kunming mice was exposed to a single-pass fractional CO(2) laser treatment. Biopsies were taken 1 h, and 1, 3, 7, 14, 28 and 56 days after treatment. Skin samples VEGF expression was evaluated by immunohistochemistry and ELISA, fibroblasts by hematoxylin-eosin staining, and types I and III collagen by ELISA. Staining for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 37 publications
1
17
0
1
Order By: Relevance
“…7and 8). These observations conform to a recent report suggesting the eff ect of irradiation promoting VEGF expression in the early stage of the wound healing 16,17) .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…7and 8). These observations conform to a recent report suggesting the eff ect of irradiation promoting VEGF expression in the early stage of the wound healing 16,17) .…”
Section: Discussionsupporting
confidence: 92%
“…At the event of anagenesis, VEGF is necessary for gingiva and bone regeneration after peri-implantitis with vascular inducer 16) . Also, CO 2 laser promotes activation of the neurogenesis of pulp cell and production of vascular endothelial growth factor (VEGF) 17,18) . As above it is necessary to carry out in a cellular level how the priodontal fibroblasts which underwent laser radiation on a titanium surface perform anagenesis as expected.…”
Section: Introductionmentioning
confidence: 99%
“…This effect may have greater clinical efficacy for scars which have maintained erythema for longer than one year and have exhibited regression of the previously described large vessels. Interestingly, the activating effect of fractional CO 2 laser was shown in an animal study to result in an initial increase in skin VEGF expression 1 and 3 days after treatment, with a decrease in levels by day 7 after treatment . This may correspond with the well‐known side effect of temporary post‐treatment erythema.…”
Section: Discussionmentioning
confidence: 95%
“…It is postulated that CO 2 laser could induce the increase of secretion of vascular endothelial growth factor and basic fibroblast growth factor. 7, 8 Nowak et al 7 showed the basic fibroblast growth factor secretion significantly increased with application more than 6 W of energy in fibroblast. However, there is still no report about vacsular endothelial growth factor secretion according to different types of laser.…”
Section: Discussionmentioning
confidence: 99%